Sulfur Dioxide: An Emerging Signaling Molecule in Plants - Li, Zhong-Guang; Li, Xiao-Er; Chen, Hong-Yan (Frontiers in Plant Science, 2022)
Sulfur dioxide (SO2) has long been viewed as toxic gas and air pollutant, but now verified as a signaling molecule in mammalian cells. SO2 can be endogenously produced and rapidly transformed into sulfur-containing compounds, such as hydrogen sulfide, cysteine, methionine, glutathione, and phytochelatin, to maintain its homeostasis in plant cells. Exogenous application of SO2 in the form of gas or solution can trigger the expression of thousands of genes. The functions of these genes are involved in the antioxidant defense, osmotic adjustment, and synthesis of stress proteins, secondary metabolites, and plant hormones, thus modulating numerous plant physiological processes. The modulated physiological processes by SO2 are implicated in seed germination, stomatal action, postharvest physiology, and plant response to environmental stresses. However, the review on the signaling role of SO2 in plants is little. In this review, the anabolism and catabolism of SO2 in plants were summarized. In addition, the signaling role of SO2 in seed germination, tomatal movement, fruit fresh-keeping, and plant response to environmental stresses, including drought, cold, heavy metal, and pathogen stresses, was discussed. The research direction of SO2 in plants was also proposed.